Mathematical modelling of cytokine dynamics in arthritic disease - Baker, Michelle (2015)
Arthritic diseases, a group of degenerative joint diseases, cause pain, disability and the loss of independence. Research over the last 30 years has improved our understanding of these conditions. We now know that these conditions are pathological in nature, and are mediated by cytokines, cell signalling proteins. We still have much to learn about disease initiation, control and progression if we wish to develop reliable and effective disease-modifying treatments.